1993
DOI: 10.1128/jcm.31.5.1209-1212.1993
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of Chlamydia trachomatis in urine specimens from symptomatic and asymptomatic men by using a rapid polymerase chain reaction assay

Abstract: Screening for Chlamydia trachomatis infection in men has traditionally been limited to men who present with urethral symptoms, thereby limiting the detection of asymptomatic chlamydia infection in men. In order to effectively screen both symptomatic and asymptomatic men, we evaluated a newly developed polymerase chain reaction (PCR) assay, Amplicor C. trachomatis, from Roche Molecular Systems for the detection of C. trachomatis in urine specimens in comparison with urethral culture. A total of 530 male urine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
2
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(100 citation statements)
references
References 19 publications
3
90
2
3
Order By: Relevance
“…113 One example can be seen in assessments of novel nucleic acid-based assays in detecting C trachomatis. 114,115 In these studies, "false positives" (DNA-amplification positive and tissue culture negative) were adjudicated by either antigen detection methods or another well-established DNA-amplification test. Despite its popularity, recent concerns have been raised regarding the potential bias incurred by discrepant analysis in favour of the new tests.…”
Section: Clinical Significance Of Positive Pcrmentioning
confidence: 99%
“…113 One example can be seen in assessments of novel nucleic acid-based assays in detecting C trachomatis. 114,115 In these studies, "false positives" (DNA-amplification positive and tissue culture negative) were adjudicated by either antigen detection methods or another well-established DNA-amplification test. Despite its popularity, recent concerns have been raised regarding the potential bias incurred by discrepant analysis in favour of the new tests.…”
Section: Clinical Significance Of Positive Pcrmentioning
confidence: 99%
“…8,9 In men, the infection accounts for 30-50% of visits to clinics for sexually transmitted diseases for non-gonococcal urethritis. 10,11 However, an often unrecognized aspect of STI, including bacterial STI, is how frequently persons with these infections have no symptoms or do not recognize the symptoms. In both genders, clinical signs and symptoms of C. trachomatis infection are mild or non-specific in up to 70% of infected cases 12 and the perpetuation of infection may be explained by describing the identified cases metaphorically as the tip of the iceberg.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of PACE 2 assay has been comparable to that of cell culture (96.7-100%), 1,2 and the Amplicor PCR has been shown to be even more sensitive than culture. [3][4][5] In a recent study, we demonstrated an equal sensitivity (90% vs. 88%) between Amplicor PCR and PACE 2 performed on cervical swab specimens obtained from a high-risk population. 6 Studies on the use of PCR with male urine specimens have demonstrated an enhanced sensitivity compared to that achieved by conventional chlamydial cell culture with urethral swab specimens.…”
mentioning
confidence: 82%